Cyclotrons as Drivers for Precision Neutrino Measurements. (22nd January 2014) - Adelmann, A.; Alonso, J.; Barletta, W. A.; Conrad, J. M.; Shaevitz, M. H.; Spitz, J.; Toups, M.; Winslow, L. A.
Abstract : As we enter the age of precision measurement in neutrino physics, improved flux sources are required. These must have a well defined flavor content with energies in ranges where backgrounds are low and cross-section knowledge is high. Very few sources of neutrinos can meet these requirements. However, pion/muon and isotope decay-at-rest sources qualify. The ideal drivers for decay-at-rest sources are cyclotron accelerators, which are compact and relatively inexpensive. This paper describes a scheme to produce decay-at-rest sources driven by such cyclotrons, developed within the DAEδ ALUS program. Examples of the value of the high precision beams for pursuing Beyond Standard Model interactions are reviewed. New results on a combined DAEδ ALUS—Hyper-K search for CP violation that achieve errors on the mixing matrix parameter of 4° to 12° are presented.